Pengaruh Distraksi Video Film Kartun Terhadap KecemasanAnak Usia 6-8 Tahun Selama Tindakan DentalDi Rs Tk Iv 04.07.02 Slamet Riyadi Surakarta - Hapsari, Adnanda Yuanggustin, Dwi Kurniawati, S.KG, MPH, drg.Naviatullaily Yarsiska (2016)
Dental anxiety on pediatric cause failure treatment because of delay treatments can makes increasingly the severity of dental condition. Anxiety comes from a sense of fear which are responded to the medulla adrenal that can stimulated the sympathetic nerves and produced eprinephrine that caused pulse rate increase. Cartoons is the one of distraction that trusted to reduce the pulse of the child anxiety during dental treatment. The aim of this study was to know the effect of visual distraction from video cartoons against children aged 6-8 years anxiety during dental treatment. The experiment was a quasi-experimental study that consist of 30 samples that divide into 2 grups, 15 children with treatment and 15 children as control. The treatment by showing video cartoons for children during treatment. The indicator of anxieties level was pulse rate and it measured using digital pulse tool (oxymeter). Data processing using independent t-test. The study showed that the mean difference pulse on control group (without using distraction video cartoon) increased as big as 5,67 meanwhile the treatment group (using distraction with cartoon) decreased as big as 10.00. The results of independent t-test analysis showed the value p = 0.000. Ho accepted when p <0.005. Based on the study, it can be summarized that there were significant differences between average pulse before and after given the distraction of video cartoon during dental treatment, which children that given the distraction had better anxiety reduction.